2000
DOI: 10.1029/2000jd900082
|View full text |Cite
|
Sign up to set email alerts
|

Influence of stratosphere‐troposphere exchange on tropospheric ozone over the tropical Indian Ocean during the winter monsoon

Abstract: Ozone (O3) and relative humidity (RH) soundings, launched over the Indian Ocean during the 1998 winter monsoon (February–March), were analyzed. In the marine boundary layer (MBL), O3 mixing ratios were relatively low (10–20 ppbv) except close to the Indian subcontinent (40–50 ppbv) where profiles were strongly influenced by pollution. Sometimes, relatively low O3 levels were observed in the upper troposphere. These were associated with deep convection in regions where MBL O3 levels were also low. In the midtro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
59
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(63 citation statements)
references
References 48 publications
4
59
0
Order By: Relevance
“…Furthermore, Folkins et al (1999) used temperature and humidity profiles to show that convection generally cannot reach altitudes above 14 km over tropical oceans. Zachariasse et al (2000) reported similar uppertropospheric layers with enhanced O 3 during the First Field Phase (FFP) of INDOEX, which took place during February and March 1998. They used trajectory analysis and potential vorticity fields derived from the European Center for Medium-Range Weather Forecast (ECMWF) to conclude that STE along the northern hemispheric subtropical jet (NH- The mid-tropospheric O 3 maxima are often associated with (very) low relative humidity (Peshin et al, 2001;Zachariasse et al, 2001).…”
Section: Introductionmentioning
confidence: 87%
See 2 more Smart Citations
“…Furthermore, Folkins et al (1999) used temperature and humidity profiles to show that convection generally cannot reach altitudes above 14 km over tropical oceans. Zachariasse et al (2000) reported similar uppertropospheric layers with enhanced O 3 during the First Field Phase (FFP) of INDOEX, which took place during February and March 1998. They used trajectory analysis and potential vorticity fields derived from the European Center for Medium-Range Weather Forecast (ECMWF) to conclude that STE along the northern hemispheric subtropical jet (NH- The mid-tropospheric O 3 maxima are often associated with (very) low relative humidity (Peshin et al, 2001;Zachariasse et al, 2001).…”
Section: Introductionmentioning
confidence: 87%
“…Figure 3a and b show vertical profiles from the 1998 IN-DOEX IFP O 3 soundings. An analysis of these profiles based on backtrajectory calculations and potential vorticity can be found in Zachariasse et al (2000). For the details of the location and time of launch of these soundings see Table 2.…”
Section: Observationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Surface sensible and latent heat fluxes are considered the main sources of q E in the atmosphere [Betts et al, 1992], while the primary sink is radiative cooling of the troposphere. Consequently, the tropical lower troposphere is characterized by a decrease in q E and an increase in O 3 with height [Folkins et al, 1999;Zachariasse et al, 2000;Betts et al, 2002]. Independent meteorological parameters such as temperature and pressure may not be conserved in downdrafts, while q E is near conservative.…”
Section: Convective Downdrafts During 18-19 September 2002mentioning
confidence: 99%
“…Because of the low frequency of in situ measurements (weekly or less), it has been hard to characterize the day-to-day variability of tropospheric ozone. Several studies based on INDOEX measurements (De Laat et al, 1999;Zachariasse et al, 2000) have dealt with short-term variability of ozone though mainly north of the equator and in the Indian Ocean, when the convective activity is maximum, and biomass burning in Southern Africa is minimum (FebruaryApril) (Cahoon et al, 1992;Barbosa et al, 1999;Arino et al, 2001).…”
Section: Introductionmentioning
confidence: 99%